Effect of Six-Sex Education Program on Social Skills in Adolescent with Intellectual Dissability in SLB N 1 Bantul - Rahmah Widyaningrum; Ignasia Nila Siwi (Universitas 'Aisyiyah Yogyakarta, 2019)
There are 1350 people with intellectual dissability in Yogyakarta, in which 50% of them are adolescent with age ranged from 13-18 years old. Most of adolescents with intellectual disability will have limitation on cognitive, adaptive behavior and social-personal function, which lead to some diverted behaviors such as inability to maintain cleanliness, taking care of themselves, and conducting good act of sexual behaviors. These conditions will lead to social perception as childish, inhuman, asexual, or bad sexual behavior due to lack of information and low cognitive function. This study aimed to assess the efect of six- sex education program on social skills of adolescent student with intellectual dissability in SLB N 1 Bantul, Yogyakarta. This is a pre experimental with one group pre test-post test design. Twenty (20) students with intellectual dissability were recruited using simple random sampling. Social skills were measured using KiSS-18 (Kikuchi’s Scale of Social Skills) questionnaire before and after six-sex education program for four weeks. The data were analyzed using paired t-test. There is a significant (p= 0.034) different on the social skills before and after six- sex education program. Adolescent with intellectual dissability require specific treatment, communication and skill to improve their social skills through sex education program.